Pengaruh Perencanaan Strategi Dan Kinerja Perusahaan Terhadap Keunggulan Bersaing Studi: Perusahaan Provider Operator Sukabumi - Devi Agustini; Erry Sunarya; Nor Norisanti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In this study, the aim was to find out whether the implementation of company strategy and performance had an influence on competitive advantage for company provider operators. The research method used in this study is a quantitative method with a sample size of 31 respondents who are Managers, Supervisors and Admins at the Sukabumi Provider Operator Company, using a saturated sampling technique. In obtaining data generated by distributing research questionnaires to all samples with a total of 30 servers regarding strategic planning variables, company performance and competitive advantage, the measurement technique used is the Likert scale. Furthermore, testing of the data that has been obtained with various tests in order to answer the hypothesis in this study. The results in this study indicate that planning has a positive and significant influence between strategy on competitive advantage, and there is a positive and significant influence between company performance on competitive advantage and simultaneously with the implementation of strategic planning and company performance can increase the position of competitive advantage in Provider Company Operators. Sukabumi.